2014
DOI: 10.1016/j.freeradbiomed.2013.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Mn porphyrin in combination with ascorbate acts as a pro-oxidant and mediates caspase-independent cancer cell death

Abstract: Resistance to therapy-mediated apoptosis in inflammatory breast cancer (IBC), an aggressive and distinct subtype of breast cancer, was recently attributed to increased superoxide dismutase (SOD) expression, glutathione (GSH), and decreased accumulation of reactive species. In the present study, we demonstrate the unique ability of two Mn(III) N-substituted pyridylporphyrin (MnP)-based SOD mimics (MnTE-2-PyP5+ and MnTnBuOE-2-PyP5+) to catalyze oxidation of ascorbate, leading to the production of excessive level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 75 publications
7
99
0
Order By: Relevance
“…A much higher yield of peroxide may be achieved if catalysts are optimized for ascorbate oxidation. Such are isomeric Mn(III) N-substituted pyridylporphyrins; their H 2 O 2 -producing potency has already been shown by us and others (82,220,273,299) (Fig. 11).…”
Section: Drug Reactivitysupporting
confidence: 52%
See 2 more Smart Citations
“…A much higher yield of peroxide may be achieved if catalysts are optimized for ascorbate oxidation. Such are isomeric Mn(III) N-substituted pyridylporphyrins; their H 2 O 2 -producing potency has already been shown by us and others (82,220,273,299) (Fig. 11).…”
Section: Drug Reactivitysupporting
confidence: 52%
“…In subsequent reoxidation of MnP with O 2 or O 2 $ -, and oxidation of ascorbate radical to dehydroascorbate, the peroxide is produced. MnP can employ peroxide and/or GSH to inactivate nuclear factor jB (NF-jB) (82,125,127,238,240), suppress mitochondrial respiration (124) and glycolysis (70,124), or induce adaptive responses (52, 75). Such pro-oxidative actions agree well with what Forman et al recently put forward as the mechanism of action of natural antioxidants (89).…”
Section: Drug Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The E. coli-based discovery of MnP-ascorbate cytotoxicity (92) brought up the idea that the combination can be used for anticancer treatment (48,95,117,130). The therapeutic potential of pharmacological doses of ascorbate alone has already been demonstrated in several preclinical and clinical trials (46,61,83,127) and is based on the increased production of reactive species due to ascorbate oxidation, catalyzed by endogenous metalloproteins (36).…”
Section: Tovmasyan Et Almentioning
confidence: 99%
“…Consequently, a maximal production of H 2 O 2 and other reactive species can be achieved, causing a more efficient tumor destruction. Promising results of such combinational catalytic therapy have been reported (48,95,130). In vitro experiments have shown that some cancer cell lines are more sensitive to either cationic MnPs or Fe porphyrins (FePs) alone and to the MnP-ascorbate combination than are normal cells (121).…”
Section: Tovmasyan Et Almentioning
confidence: 99%